Building resilience in health and social care teams. Issue 6 (5th September 2016) - McCray, Janet; Palmer, Adam; Chmiel, Nik
Abstract : Purpose: Maintaining user-focused integrated team working in complex care is one of the demands made of UK health and social care (H&SC) organisations who need employees that are resilient, resilience being the ability to persevere and thrive in the face of exposure to adverse situations (Rogerson and Ermes, 2008, p. 1). Grant and Kinman (2012) write that resilience is a complex and multi-dimensional construct that is underexplored in social care team work. The purpose of this paper is to capture the views of managers in H&SC to explore the making of resilient teams, identify factors that influence team performance and inform organisational workforce development strategy. Design/methodology/approach: A general inductive approach (Silverman, 2011) was applied. Five focus groups were facilitated ( n =40) each with eight participants all of whom were leaders and managers of teams in H&SC, working in the integrated care context in the UK. Findings: Findings indicate that further investment in strategies and resources to sustain and educate employees who work in teams and further research into how organisational systems can facilitate this learning positively may contribute to resilient teams and performance improvement. The authors note specifically that H&SC organisations make a distinction between the two most prevalent team types and structures of multi-disciplinary and inter-professional and plan more targeted workforce development for individual and team learning for resiliency within these team structures. In doing so organisations may gain further advantages such as improved team performance in problematic care situations. Research limitations/implications: Data captured are self-reported perceptions of H&SC managers. Participant responses in the focus group situation may have been those expected rather than those actually modelled in the realities of team work practice (Tanggaard, 2008). Further, in the sample all participants were engaged in a higher education programme and it is possible participants may have been more engaged with their practice and thinking more critically about the research questions than those not currently undertaking postgraduate study (Ng et al., 2014). Nor were the researchers able to observe the participants in team work practice over time or during critical care delivery incidents. Practical implications: The preliminary link made here between multi-disciplinary and inter-professional team type, and their different stress points and subsequent workforce intervention, contributes to the theory of resilient teams. This provides organisations with a foundation for the focus of workplace learning and training around resilience. H&SC practitioner views presented offer a greater understanding of team work processes, together with a target for planning workforce development strategy to sustain resilience in team working. Originality/value: This preliminary research found that participants in H&SC valued the team as a very important vehicle for building and sustaining resilience when dealing with complex H&SC situations. The capitalisation on the distinction in team type and individual working practices between those of interprofessional and multidisciplinary teams and the model of team learning, may have important consequences for building resilience in H&SC teams. These findings may be significant for workforce educators seeking to develop and build effective practice tools to sustain team working.